The Effectiveness of Group Guidance Using Anti-Bullying Puzzle Media on Junior High School Students Awareness of Bullying Behavior - Futihaturrobiah Futihaturrobiah; Farida Agus Setiawati (Madania: Jurnal Ilmu-Ilmu Keislaman, 2026)
This study aims to examine the effectiveness of group guidance services utilizing anti-bullying puzzle media in improving junior high school students’ awareness of bullying behavior. Bullying remains a prevalent issue in educational settings, particularly at the junior high school level, where students often demonstrate limited awareness of its forms and impacts, leading to the persistence and normalization of such behavior. To address this problem, a quantitative approach with a quasi-experimental pretest–posttest control group design was employed. The participants consisted of 40 eighth-grade students from SMP Negeri 6 Metro, selected through purposive sampling and divided into an experimental group and a control group, each comprising 20 students. The experimental group received group guidance services integrated with anti-bullying puzzle media, while the control group received conventional group guidance without the media. Data were collected using a 25-item bullying awareness questionnaire with confirmed validity and reliability (Cronbach’s Alpha > 0.70). Data analysis included paired sample t-tests, independent sample t-tests, and N-Gain analysis. The results indicated that both groups experienced significant improvements in bullying awareness; however, the experimental group showed a significantly higher increase compared to the control group. The posttest results revealed a significant difference between groups (p < 0.05), and the N-Gain score in the experimental group was categorized as moderate, while the control group was in the low category. These findings suggest that the integration of anti-bullying puzzle media enhances the effectiveness of group guidance services by promoting active participation, engagement, and deeper understanding. In conclusion, anti-bullying puzzle media can serve as an innovative and effective approach in preventive guidance and counseling services to improve students’ awareness of bullying behavior in schools.